الحبس المنزلي - بلليش, الفت (Latakia University Journal - Economic and Legal Sciences Series, 2018)
HOME CONFINEMENT IS; accusation the offender staying in his home, or any specific place for period of time. Maybe in some countries from7 to 7 oclock. On condition permitting him practicing his dally activities, studying, or acting. If a judge rules that an offender qualifies for electronic monitoring, then he or she can reduce or eliminate jail time altogether. For repeat offenders, electronic monitoring may be administered in addition to jail time. Electronic monitoring allows offender who is sentenced to jail time to serve the time at home instead of in prison. Generally speaking, the offender is allowed to go to school or work as long as curfew is obeyed. The individual is also permitted to go to Narcotics Anonymous meetings, court appearances, court-ordered education classes, and any other places required as part of probation. The time spent wearing an electronic monitoring is usually equal to the length of the jail sentence, but in some cases, it could be longer. يقوم هذا النظام على إلزام الخاضع له بالبقاء في منزله أو محل إقامته لفترة محددة من الزّمن, تُحدد في بعض الدّول من السابعة مساءً إلى السابعة من صباح اليوم التالي, على أن يسمح له بممارسة أعماله الاعتياديّة في الساعات الخارجة عن المراقبة كأن يذهب للدراسة أو يزاول مهنة. ففي حال قرر القاضي صلاحية الجاني للخضوع لنظام الحبس المنزلي, يمكن له أن يحكم بإلغاء عقوبة الحبس, أو الاستعاضة عن جزءٍ منها بتطبيق هذا النّظام. ويحدد القرار الصادر عن القاضي المختص بالخضوع لنظام الحبس المنزلي الأماكن التي يمكن للجاني الذّهاب إليها, والأوقات التي يمكنه الخروج من المنزل خلالها. وبالتالي يمكن للخاضع لنظام الحبس المنزلي متابعة دراسته, والذّعاب للعمل, والمثول أمام المحاكم. شريطة أن يكونم القرار القضائي قد تضمّن ذلك, وأن يخضع الجاني لجميع الالتزامات المكلّف بها من قبل القاضي. وعادةً تكون مدة الخضوع لنظام الحبس المنزلي مساويةً للمدة المحكوم بها للبقاء في السّجن. إلا أنّ هنالك حالاتٍ معينةً تكون فيها مدّة الخضوع لنظام الحبس المنزلي أطول من المدّة المحكوم بها بالحبس. وذلك يكون تبعاً لقوانين الدولة, ونوع الجريمة التي فرض نظام الحبس المنزلي كعقوبةٍ لها.